INTERJEKSI HA! DALAM FILM TENGGELAMNYA KAPAL VAN DER WIJCK: PENDEKATAN SEMANTIK METABAHASA ALAMI - Dian Syaputra; Mulyadi Mulyadi (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2022)
Interjection is a word used to express feelings or something spontaneously. In Indonesian there are many interjection words, but here what will be discussed is an interjection HA! which can be used in various spontaneous expressions. Not only that, Interjection HA! have similarities and differences with interjections in other Indonesian languages. This study aims to find the meaning of the Ha! which is used in the film "The sinking of the Van Der Wijck ship" a work by a famous writer from Padang, namely Buya Hamka. This research uses a Natural Metalanguage Semantic approach, and this study uses a qualitative descriptive research method with listening and note-taking techniques. Data were collected by watching or viewing the film or by listening to conversations containing the Ha! in the film. Furthermore, the data from the results of this study, it was found that there were 6 meanings of the Ha! in the film "The sinking of the Van Der Wijck ship" namely Emotive Interjection Ha! which shows feelings of pleasure or happiness, angry, disappointed, suspicious, surprised, and Kogitive Interjection Ha! funny (laughing out loud).